Ten Challenges and Recommendations for Advancing Research on the Effects of College on Students - Tricia A. Seifert; Nicholas A. Bowman; Gregory C. Wolniak; Alyssa N. Rockenbach; Matthew J. Mayhew (SAGE Publishing, 2017)
The first two volumes of How College Affects Students constitute the most-cited publications in higher education research. Since these volumes were published, the literature on college impact has expanded greatly, which is at least partially the result of the nearly 500 journals focusing on the scholarship of teaching and learning internationally. In addition to the increase in the quantity of college impact research, methodological advancements and the changing notion of the higher education enterprise have further shaped the rigor and tenor of the literature. We draw on our experience and lessons learned from conducting the most recent comprehensive synthesis of college impact literature to discuss 10 challenges and corresponding recommendations to advance future research of the effects of college on students.